Identification of antioxidative ingredients from feverfew (Tanacetum parthenium) extract substantially free of parthenolide and other alpha-unsaturated gamma-lactones - Fa Zhang; Jianyun Zhou; Yiqun Shi; Ken Karaisz (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
Extract of feverfew (Tanacetum parthenium) has anti-inflammatory effect with various therapeutic benefits. Alpha-unsaturated gamma-lactones including parthenolide were recognized as part of the major active ingredients but with undesirable allergic reactions. In this research paper, feverfew extract substantially free of parthenolide and other alpha-unsaturated gamma-lactones was investigated.